Voltage Control of Single-Phase Two Winding Self Excited Induction Generator Using SVC-MERS for Isolated System - Fransisco Danang Wijaya; Hartanto Prabowo (Institute of Advanced Engineering and Science, 2016)
Single-phase induction generator is very suitable to be used in the typical loads which only need a single-phase power supply with small power capacity requirement, such as diesel engine, picohydro or small wind plant. It has some advantages such as rugged, effective cost, maintenance free and require no external excitation. However, it has inductive characteristic which makes poor voltage regulation. This paper proposed a shunt reactive compensator called SVC-MERS which can provide a variable reactive power to maintain the generator voltage despite of load variations. The experiment was conducted on single-phase two winding induction generator coupled by a three-phase induction motor which serves as the prime mover. SVC-MERS and the load are connected in shunt to the main winding, while the excitation capacitor was connected to the auxiliary winding. The experimental results showed that SVC-MERS can improve voltage regulation and substantially enhanced steady state loading limit.